Natural dead sea salt and retrospective dosimetry - Norfadira, W.; Abdul Sani, S. F.; Ain, R.; Ismail, S. S.; Muhammad, H. A. J.; Khandaker, Mayeen Uddin *; Daar, E.; Almugren, K.S.; Alkallas, F.H.; Bradley, D. A. * (Springer, 2020)
Accidents resulting in widespread dispersal of radioactive materials have given rise to a need for materials that are convenient in allowing individual dose assessment. The present study examines natural Dead Sea salt adopted as a model thermoluminescence dosimetry system. Samples were prepared in two different forms, loose-raw and loose-ground, subsequently exposed to 60Co gamma-rays, delivering doses in the range 2–10 Gy. Key thermoluminescence (TL) properties were examined, including glow curves, dose response, sensitivity, reproducibility and fading. Glow curves shapes were found to be independent of given dose, prominent TL peaks for the raw and ground samples appearing in the temperature ranges 361–385 ºC and 366–401 ºC, respectively. The deconvolution of glow curves has been undertaken using GlowFit, resulting in ten overlapping first-order kinetic glow peaks. For both sample forms, the integrated TL yield displays linearity of response with dose, the loose-raw salt showing some 2.5 × the sensitivity of the ground salt. The samples showed similar degrees of fading, with respective residual signals 28 days post-irradiation of 66% and 62% for the ground and raw forms respectively; conversely, confronted by light-induced fading the respective signal losses were 62% and 80%. The effective atomic number of the Dead Sea salt of 16.3 is comparable to that of TLD-200 (Zeff 16.3), suitable as an environmental radiation monitor in accident situations but requiring careful calibration in the reconstruction of soft tissue dose (soft tissue Zeff 7.2). Sample luminescence studies were carried out via Raman and Photoluminescence spectroscopy as well as X-ray diffraction, ionizing radiation dependent variation in lattice structure being found to influence TL response.